2020
DOI: 10.30621/jbachs.2020.1305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesenchymal Stem Cells on Cochlear Cell Viability After Cisplatin Induced Ototoxicity

Abstract: Aims: Ototoxicity is one of the main side effects of the chemotherapeutic agent Cisplatin (CDDP). CDDP ototoxicity is caused by damage of the organ of Corti, spiral ganglion cells or lateral wall (stria vascularis and spiral ligament). Mesenchymal stem cells (MSCs) were shown to differentiate into neurogenic and auditory hair cells in vitro. In this study, effect of MSCs in CDDP ototoxicity model of HEI-OC1 cochlear cells was evaluated. Method:The cochlear cells were exposed to 50 and 100 microM CDDP for 24, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The study induced ototoxicity with 100 uM CDDP and administered MSC with 40% difference identified in viability of cochlear cells after incubation. It was identified that MSC reduced the cochlear cell injury caused by CDDP [16]. In light of these findings, our hypothesis in this study is that systemic MSC administered with CDDP for NB will reduce the ototoxicity side effect and not change the anticancer efficacy.…”
Section: Introductionmentioning
confidence: 80%
“…The study induced ototoxicity with 100 uM CDDP and administered MSC with 40% difference identified in viability of cochlear cells after incubation. It was identified that MSC reduced the cochlear cell injury caused by CDDP [16]. In light of these findings, our hypothesis in this study is that systemic MSC administered with CDDP for NB will reduce the ototoxicity side effect and not change the anticancer efficacy.…”
Section: Introductionmentioning
confidence: 80%